Results of research on the formation of students readiness to keep the professional ethics - Natalia V. Ageyenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the problem of training qualified specialists in journalism. It is noted, in the present conditions of development of society it is necessary to develop spiritually rich personality possessing creativity, high professional culture, morality. The author presents the results of the research on the formation of readiness of future journalists to abide by professional ethics. It is revealed the necessity of the use of a foreign language as a mean of development indicators of readiness of students to professional work components. Analyzing the concept of a three-tier structure of linguistic personality, it is defined as the correlation between the three types of communication needs as well as the three sides of the communication process - communicative, interactive and perceptive, reflecting the nature of activities of a journalist and is closely related to its functions. The article suggests the algorithm formation of professionally significant qualities of students in different activities.